Revisiting dysanapsis: Sex-based differences in airways and the mechanics of breathing during exercise - Sheel, W. A.; Dominelli, P. B.; Molgat-Seon, Y. (Experimental Physiology, 2015)
Our understanding of the human ventilatory response to exercise is largely based on a historical body of literature focused primarily on male rather than female research subjects. In recent years, important sex-based differences in the anatomy of the human respiratory system have been identified; for a given lung size, women appear to have smaller diameter conducting airways than men. The presence of such inherent differences in the tracheobronchial tree greatly affects the mechanics of airflow generation, especially during conditions of high ventilation rates such as exercise. Data from a growing number of studies suggests that women may be more susceptible to respiratory system limitations during exercise than their male counterparts. Specifically, women are more likely to experience expiratory flow limitation, exercise-induced arterial hypoxaemia, and have a higher metabolic cost of breathing for a given ventilation. Collectively, the available evidence suggests that sex-differences in the ventilatory response to exercise are present and may have important ramifications on the integrated response to exercise, however, several fundamental questions remain unanswered.